Periodontal manifestations of local and systemic diseases : colour atlas and text - Laskaris, George; Scully, C. M; Tatakis, Dimitris N; Lindhe, Jan (Springer, 2003)
The main purpose of the book is to satisfy the dentist\'s interest in the diseases of the oral cavity through a to pographic approach. The atlas-like presentation follows a well-defined structure concerning etiology, gingival involvement, clinical features, differential diagnosis and treatment. Contains 400 excellent illustrations and is formatted for easy reference on a day-to-day basis.
Keywords: parodontitida; nemoci parodontu; Periodontics; Periodontitis; Periodontal Diseases; zubní lékařství; parodontologie